2017
DOI: 10.1111/pala.12330
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic methods surpass parsimony when assessing clade support in phylogenetic analyses of discrete morphological data

Abstract: Fossil taxa are critical to inferences of historical diversity and the origins of modern biodiversity, but realizing their evolutionary significance is contingent on restoring fossil species to their correct position within the tree of life. For most fossil species, morphology is the only source of data for phylogenetic inference; this has traditionally been analysed using parsimony, the predominance of which is currently challenged by the development of probabilistic models that achieve greater phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 25 publications
(60 reference statements)
1
97
0
Order By: Relevance
“…; O'Reilly et al . ). The accuracy of these maximum likelihood trees can be improved by accounting for uncertainty using bootstrapping and subsequent collapsing of poorly‐supported branches into polytomies (Brown et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; O'Reilly et al . ). The accuracy of these maximum likelihood trees can be improved by accounting for uncertainty using bootstrapping and subsequent collapsing of poorly‐supported branches into polytomies (Brown et al .…”
Section: Discussionmentioning
confidence: 97%
“…; O'Reilly et al . ). The use of bootstrapping could be incorporated into similar comparisons between inferred trees and informal composite trees in the future, but at present the use of bootstrapping with this method would cause problems of pseudoreplication, as the input trees are assumed to be independent, but this is not the case with data from bootstrapping as they are based on partially overlapping data.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, perceptions of ‘key characters’ have invariably been formulated within the increasingly out‐moded parsimony‐based phylogenetic framework (Wright & Hillis, ; O'Reilly et al ., , ; Puttick et al ., ) used to infer both seed plant relationships and the phylogenetic distribution of characters. Symptomatically, much of the controversy over seed plant relationships is rooted in the false precision of parsimony‐based phylogenetic analyses of morphological characters (O'Reilly et al ., , ; Puttick et al ., ). At the least, the hypotheses of character evolution used to discriminate stem‐ and crown‐angiosperm fossil taxa should be reviewed within a probabilistic framework that can better accommodate the uncertainty associated with such inference.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at least for the data set analysed by the authors, priors and MCMC proposals were not an issue. Although both probabilistic methods are comparable in building trees from morphology (O'Reilly et al ., ), differently from BI, the formal analysis of phylogenetic information under ML was studied more thoroughly (Massingham & Goldman, ; Geuten et al ., ; Mauro et al ., ). If the BI‐ML equivalence demonstrated by Brown et al .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers were thus prompted to investigate the performance of Markovian models in estimating phylogenetic relationships relying on morphological data when compared to the widely used parsimony approach. Previous simulation studies have shown that the Bayesian model‐based inference provides more accurate phylogenetic trees than the parsimony algorithms across a range of different conditions (Wright & Hillis, ; O'Reilly et al ., , ). However, such accuracy comes at the cost of poor precision, as the recovered Bayesian consensus trees are largely unresolved (Brown et al ., ; O'Reilly et al ., ).…”
Section: Introductionmentioning
confidence: 99%